The Role of Donation-Based Crowdfunding Platforms in Improving People's Welfare (Study on the Kitabisa.com) - Maria Anna Muryani; Noor Rosyidah; Maliki Alfajr Davin C.S; Afif Noor (JED (Jurnal Etika Demokrasi), 2023)
Indonesia is a welfare state that is responsible for the welfare of its citizens, this is not an easy thing with high levels of poverty and corruption. It takes the participation of all components of the nation to realize this welfare. The object of this study is to determine the role of donation-based crowdfunding (DCF) platforms in improving people's welfare by focusing on the Kitabisa.com platform. In this study, the problem formulation is the extent to which DCFs such as Kitabisa.com can contribute to improving community welfare. The research method used is qualitative by collecting data through printed and online documents. The results showed that DCF platforms, particularly Kitabisa.com, have helped individuals resolve financial burdens and made it easier for the community to access donations. DCF has a significant role in facilitating financial assistance for individuals and communities in need and is very effective in connecting donors and recipients, providing an easy-to-use interface, and ensuring transparency in the donation process that can have implications for improving people's welfare.